Ecological factors affecting wetland occupancy by breeding Anatidae in the southwestern mediterranean. Issue 2 (6th February 2017) - Cherkaoui, Sidi Imad; Selmi, Slaheddine; Hanane, Saâd
Abstract: Conservation of Anatidae in North Africa is hindered by lack of information concerning population size, population trends, and species‐habitat relationships. In this work, we used a 2‐year survey data in 25 wetlands distributed throughout Morocco to model duck spatial distribution and to assess the relevance of a set of environmental and anthropogenic factors in predicting site occupancy, by means of Generalized Linear Mixed Models (GLMM). Mallards and Ferruginous ducks were the most commonly detected species, whereas White‐Headed Ducks and Common Pochards were the least detected ones. An inter‐annual variation in site occupancy was recorded for Ruddy Shelducks, Red‐Crested Pochards and White‐Headed Ducks. Geographical location (measured mainly as distance to the coastline and altitude) was the major predictor of the occurrence probability of Ruddy Shelducks, Marbled Teals and Red‐Crested Pochards, while human presence and habitat features were the most relevant factors in shaping Mallard's distribution. However, none of the considered environmental and anthropogenic factors explained the distribution patterns of the Ferruginous Duck, Common Pochard and Gadwall. The results of this study clearly show that there are still gaps in our knowledge on factors driving wetland occupancy by breeding Anatidae in Morocco. The pursuit of the investigations, while considering other explanatory factors such as water quality (limnological data), diet, predation, and conservation status, is of great importance to more profoundly understand the dynamics of Moroccan duck populations.